In vitro anti-Trypanosoma cruzi activity of essential oils of ten medicinal plants - Rojas, Juan (2010)
Objectives: To determine in vitro anti-Trypanosoma cruzi activity of essential oils of 10 plants, cytotoxic activity of oils against mammalian cells and modulatory activity of oils on nitric oxide. Design: In vitro analytical-experimental research, prospective longitudinal cutting. Setting: Institute of Clinical Research, and Institute of Tropical Medicine, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Trypanosoma cruzi epimastigotes; Raw 264.7 cells; ten medicinal plants: Mentha X piperita L (menta), Rosmarinus officinalis L (romero), Chenopodium ambrosioides L (paico), Eucaliptus globulus Labill (eucalipto), Artemisia absinthium L (ajenjo), Melissa officinalis L (toronjil), Minthostachys setosa Brig (muña), Cimbopogon citratus (hierba luisa), Aloysia triphylla (cedrón), and Mentha spicata L (hierba buena). Methods: The trypanocidal activity was assessed against epimastigotes grown in LIT medium, incubated for 48 hours at 37ºC in humidified incubator with 5% CO2. Crystal violet was used as positive control. The cytotoxic activity of products against mammalian cells was assessed in RAW 264.7 cells and the modulatory activity of compounds on nitric oxide was also measured in cultured RAW 264.7 cells. Main outcome measures: Percentage inhibition of viability and IC50. Results: Essential oils of Cymbopogon citratus (lemon verbena) and Aloysia triphylla (lemon verbena) inhibited the growth of T. cruzi epimastigote form with good IC50s of 63.09 and 96.49 mg/mL, respectively. There was no significant variation in the concentration of nitric oxide and no cytotoxicity was evident. Conclusions: Essential oils of Aloysia triphylla and Cymbopogon citratus showed anti-Trypanosoma cruzi activity in vitro and were not cytotoxic to mammalian cells.